Metformin Ameliorates Postoperative Cognitive Dysfunction through Regulation of the AMPK/SIRT1 Pathway - Peiyu Jia; Ji Che; Junfeng Zhang; Haibing Li; Quanhong Zhou; Yong Guo (Journal of Integrative Neuroscience, 2023)
Background: Postoperative cognitive dysfunction (POCD) is a common postoperative complication in elderly patients. The purpose of this study was to investigate the mechanism through which metformin improves postoperative cognitive function. Methods: In the in vivo experiment, 18-month-old Sprague–Dawley (SD) rats were randomly divided into four groups (n = 12 in each group): the control, metformin, operation, and operation plus metformin groups. The animals were pretreated with metformin by gavage once daily for two weeks. The Morris water maze (MWM) was used to measure cognitive ability. In the in vitro experiment, BV2 cells were divided into five groups: the control, metformin, lipopolysaccharide (LPS), LPS plus metformin, and LPS plus metformin plus compound C groups. We stimulated microglia with LPS (500 ng/mL). Immunofluorescence and Western blotting were used to assess ROS (reactive oxygen species) levels, autophagy-associated protein levels and adenosine monophosphate-activated protein kinase (AMPK)/regulator factor 2-related enzyme 1 (SIRT1) signaling pathway activity in the rat cortex and microglial cells. Results: In the MWM test, the metformin-pretreated rats spent a higher proportion of time in the target quadrant. Immunofluorescence showed that the fluorescence intensity of LC3 in the cortex was increased in rats pretreated with metformin. Western blotting indicated that metformin upregulated the expression of autophagy-related and AMPK/SIRT1 signaling pathway-related proteins in the cortex after surgery. By activating the AMPK/SIRT1 signaling pathway in vitro, metformin reduced microglial activation and oxidative stress and promoted autophagy. Conclusions: Through the AMPK/SIRT1 pathway, metformin can boost autophagy and reduce oxidative stress in cortical microglia in older rats, in turn improving postoperative cognitive function.